PELAKSANAAN UPACARA ADAT PERKAWINAN MASYARAKAT MADURA DI DESA SUNGAI RAYA DALAM KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - NIM. A1012191002, BEHRIYEH (Fakultas Hukum Universitas Tanjungpura, 2022)
Abstrac The traditional wedding ceremony has existed from ancient times which was passed down by the ancestors, in Madurese society the traditional wedding ceremony consists of 15 series, namely before the Kabul consent, which consists of tan-pentan mar-lamar, les-bhales, kon-lakon/lalakon, terop/ tatarok, teppongan, lek-mellek, bhubuwan and after Kabul's consent, namely consisting of kabinan, mantan, ngereng mantan, onjhang mantoh, ontalan, gha'-nanggha, and ghun-tengghun, because the times are growing and then affect social change in society so that in the implementation of the Madurese Community Traditional Marriage Ceremony in Sungai Raya Dalam Village, Sungai Raya Subdistrict, Kubu Raya Regency, there was a shift, namely in the traditional ceremony before the Kabul consent, namely terop or tatarok, lek-mellek and after the Kabul consent, namely ontalan.The formulation of the problem in this study